Effects of walking interventions in persons with multiple sclerosis-A systematic review - Boková, Ivana; Gaemelke, Tobias; Novotná, Klara; Hvid, Lars G; Dalgas, Ulrik (Multiple sclerosis and related disorders, 2024)
OBJECTIVE: The aim of the present systematic review was to investigate the effects of voluntary walking interventions in persons with multiple sclerosis (pwMS). For this purpose, we developed a framework to describe the components of walking interventions. DATA SOURCES: Two databases (MEDLINE/PubMed and EMBASE) were searched in January 2023. STUDY SELECTION: Included studies enrolled pwMS and evaluated walking interventions with a duration of 2 weeks or longer. Further, they evaluated at least one walking-related outcome. Both RCTs and non-controlled studies were enrolled. DATA EXTRACTION: Data were extracted using a customized spreadsheet, which included detailed information on patient characteristics, interventions, outcomes, and results. Based on the extracted results, the effect sizes (ES, Hedge's g) of the walking interventions were calculated if possible. The methodological quality of the included studies and their reporting was determined using the TESTEX evaluation tool. DATA SYNTHESIS: Data from a total of n = 200 pwMS was included from N = 7 RCT ́s (from 3 we used within-group data) and N = 5 single-group studies. On average 91.7 ± 9.9 % of the planned walking sessions were attended, 8.7 ± 10.5 % of the participants dropped out, and very few adverse events occurred. Walking interventions improved walking performance during short distance walk tests (ES ranging from -0.21 to -0.72, "walking time") and long distance walk tests (ES ranging from 0.27 to 0.72, "walking distance"). CONCLUSIONS: Voluntary walking interventions appear to be safe and effective at improving walking performance in pwMS. However, well-powered walking intervention studies are needed to confirm these promising effects. The simplicity of walking interventions makes them highly relevant for ambulatory pwMS.
Keywords: roztroušená skleróza; test chůzí; Walk Test; Multiple Sclerosis; Humans; Walking; chůze; lidé